Den anderen einen Schritt voraus: Interview mit Hans Christoph Meuli - Ingold, Niklaus; Ochsner, Peter E.; Steinke, Hubert (Maurice E. Müller und die Entwicklung künstlicher Hüftgelenke in der Schweiz. Zeitzeugenbefragungen zur Geschichte einer Medizintechnik, 2023)
Hans Christoph Meuli worked as an assistant physician and senior physician to Maurice E. Müller from 1960 at the Orthopaedic Clinic at St. Gallen Cantonal Hospital and from 1966 as senior physician and deputy head at the Orthopaedic University Clinic at Inselspital Bern. In 1968 he opened a private practice at the Lindenhofspital. In 1976, the Department of Education of the Canton of Berne appointed him a private lecturer in orthopaedics. He was promoted to honorary professor in 1982. He later became an honorary professor.